- Efektivitas Project-Based Learning untuk Meningkatkan Keterampilan Berpikir Kritis - Dara Mutiara Aswan; Mia Aina; Desfaur Natalia (Jurnal Penelitian Pendidikan IPA, 2024)
The era of industrial revolution 4.0 requires us to be "familiar" with the digital world. Not just doing hobbies, people can even do work with the help of digital tools. In facing challenges in the digital era in the form of a rapid flow of information, critical thinking skills are really needed. Students' critical thinking skills need to be trained to solve contextual problems, one of which is through implementing Project Based Learning (PjBL) in learning. This research aims to see the effectiveness of PjBL on students' critical thinking skills. This research is a quasi-experimental research with a one group pretest-post-test design. The population in this study were undergraduate students of the Biology education program in Universitas Jambi. The instrument used in this research is essay questions along with a rubric for assessing critical thinking skills. Data were analysed using SPSS 25.00 software. The results of the analysis show that there is a significant difference between the pretest and post-test scores for students' critical thinking abilities. It can be concluded that PjBL is effective in improving critical thinking skills.